Effects of short-term inactivity on glucose tolerance, energy expenditure, and blood flow in trained subjects - Arciero, P. J.; Smith, D. L.; Calles-Escandon, J. (Journal of Applied Physiology, 1998)
The purpose of this investigation was to examine the effects of 7-10 days of inactivity (IA) on glucose tolerance (GT), resting metabolic rate (RMR), thermic effect of a meal (TEM), and limb blood flow in endurance-trained men. Eight highly trained (peak O2 consumption 64 +/- 2 ml . kg-1 . min-1) endurance athletes participated in this study involving two identical test days, one approximately 24 h after a normal training bout (Tr) and the second after 7-10 days of IA. The following tests were conducted at each visit: 75-g oral glucose tolerance test (OGTT), RMR, and TEM and measurements of calf and forearm blood flow (BF) by using venous occlusive plethysmography. Body weight remained unchanged during this short period of IA (Tr, 78.5 +/- 1 kg; IA, 78.7 +/- 1 kg). The area under the glucose and insulin curves increased 65% (Tr, 3,375 +/- 877 vs. IA, 5,559.4 +/- 621 mg . dl-1 . 180 min-1) and 73% (Tr, 2,182.5 +/- 270 vs. IA, 3,793.1 +/- 739 microU . ml-1 . 180 min-1) after IA, respectively (P < 0.01). RMR decreased significantly (4%; 1.5 +/- 0. 02 vs. 1.44 +/- 0.02 kcal/min; P < 0.05) and respiratory exchange ratio during the OGTT increased (4%, 0.812 +/- 0.011 vs. 0.842 +/- 0. 009; P < 0.05) after IA, whereas TEM increased similarly in the Tr and IA states. In the Tr state, mean calf BF increased by 22% (3.17 +/- 0.22 vs. 3.87 +/- 0.38 ml . 100 ml-1 . min-1; P < 0.05) during the OGTT but remained unchanged after IA, whereas no differences at rest or during OGTTs existed between the two conditions for forearm BF. Incremental insulin area above fasting during the OGTT was correlated with mean calf BF in the Tr (r = 0.76, P < 0.05) and IA (r = 0.72, P < 0.05) states. In conclusion, 7-10 days of IA results in a deterioration in GT and a reduction in RMR. After glucose ingestion, calf BF was elevated compared with resting levels in the Tr state but was unchanged in the IA state; however, limb BF was not related to GT or RMR. Thus our findings raise questions regarding the relative contribution of BF in modulating glucose tolerance and energy expenditure in endurance athletes in their habitual Tr or IA state.